A double-blind, randomize, placebo-control trial to evaluate the effect of Nigella sativa on palmar arsenical keratosis patients (Bangladesh Journal of Pharmacology, 2014)
This study was done to examine the role of Nigella sativa in 28 patients of palmar arsenical keratosis. Patients were randomized into two groups: Group A (n-15) receive capsules of placebo and vitamin E (200 mg) whereas Group B (n= 13) receive capsules of N. sativa oil (500 mg) and vitamin E (200 mg) orally for 8 weeks. The mean (± SD) clinical scoring of palmer arsenical keratosis in Group A before and after treatment was 99.3 ± 21.5 and 62.3 ± 14.3 respectively (37% reduction). On the other hand, in N. sativa oil treated group, the mean clinical score was 119.1 ± 20.3 before treatment which was reduced to 39.2 ± 8.4 (p